Community Preparedness Behavior of Air Manis Subdistrict, Padang City in Facing Earthquake Disasters - Andria Putra, Gisky; Widuri, Nike; Effendi, Midiansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
Education on earthquake disasters plays a role in providing the community with basic knowledge about what should be done before, during, and after an earthquake occurs. This study aims to describe the knowledge, attitudes, and skills of the community in facing earthquake disasters. The research was conducted in Air Manis sub-district, Padang city. This study employed a survey design with a quantitative approach and used a Likert scale as the measurement instrument. Data analysis techniques were carried out using SPSS software. The results showed that the majority of the community’s cognitive level regarding earthquake disasters fell into the high category with a percentage of 59.1%, the affective level of the majority was in the very high category with a percentage of 89.8%, and the psychomotor level of the majority was also in the very high category with a percentage of 83%. These findings indicate that the majority of the Air Manis community in Padang city has a very good level of preparedness in earthquake disaster mitigation. Nevertheless, continuous education programs, simulations, and training are still needed to ensure that the community’s knowledge, attitudes, and skills do not decline and become more evenly distributed.